2022
DOI: 10.3389/fphar.2022.842720
|View full text |Cite
|
Sign up to set email alerts
|

Stewed Rhubarb Decoction Ameliorates Adenine-Induced Chronic Renal Failure in Mice by Regulating Gut Microbiota Dysbiosis

Abstract: This study aimed to investigate the protective effect of Stewed Rhubarb (SR) decoction on chronic renal failure (CRF) through the regulation of gut microbiota. Using a CRF mouse model induced by a 0.2% adenine diet, we proved that SR decoction (2.0 g crude SR/kg) significantly reduced the levels of urea and creatinine in plasma of CRF mice, accompanied by the improvement of renal fibrosis and tubular atrophy, amelioration of inflammation, and inhibition of aquaporins damage. Also, SR decoction alleviated gut b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…In a previous study, we found that using a combination of four antibiotics (ampicillin at 1.0 mg/mL, vancomycin at 0.5 mg/mL, neomycin sulfate at 1.0 mg/mL, and metronidazole at 0.5 mg/mL) dissolved in drinking water was an effective method for depleting gut microbiota [ 29 ]. This method has been widely used by researchers and documented in several publications [ [29] , [30] , [31] , [32] ]. For the Ctrl and MPTP groups, mice were fed with sterile water, and the other two groups were treated with Ab (1.0 mg/mL ampicillin, 0.5 mg/mL vancomycin, 1.0 mg/mL neomycin sulfate, and 0.5 mg/mL metronidazole, dissolved in drinking water) for 12 weeks in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we found that using a combination of four antibiotics (ampicillin at 1.0 mg/mL, vancomycin at 0.5 mg/mL, neomycin sulfate at 1.0 mg/mL, and metronidazole at 0.5 mg/mL) dissolved in drinking water was an effective method for depleting gut microbiota [ 29 ]. This method has been widely used by researchers and documented in several publications [ [29] , [30] , [31] , [32] ]. For the Ctrl and MPTP groups, mice were fed with sterile water, and the other two groups were treated with Ab (1.0 mg/mL ampicillin, 0.5 mg/mL vancomycin, 1.0 mg/mL neomycin sulfate, and 0.5 mg/mL metronidazole, dissolved in drinking water) for 12 weeks in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Bile acids (BAs) were extracted and analyzed in accordance with previously established methodologies [25] .…”
Section: Detection Of Bile Acidsmentioning
confidence: 99%
“…In recent years, increasing evidence has demonstrated the important role of the gut–kidney axis in the progression of CKD, where one important risk factor is endotoxins. Excessive intake of high-fat and high-sugar diets can cause an imbalance in gut microbiota and intestinal barrier dysfunction, resulting in an increase in circulating endotoxin concentrations. High concentrations of endotoxins have been closely linked to innate immune responses, which not only worsen obesity-associated metabolic disorders but also lead to renal damage via endotoxin-driven pathways. , It is worth noting that Toll-like receptor 4 (TLR4) is found to be the primary molecule through which endotoxins activate the IκB kinase (IKK)/nuclear factor kappa-B kinase (NF-κB) pathway, thereby causing renal inflammation progression through the release of cytokines. These recent advances provided new insight into finding functional ingredients for the prevention and management of obesity-related kidney injury. …”
Section: Introductionmentioning
confidence: 99%